Genetic landscape of Italian SRLV: insights from passive surveillance-based phylogenetic analysis - Gobbi, Paola; Tassoni, Luca; Tinelli, Elena; Scoccia, Eleonora; Mrabet, Sara; Orrico, Mario; Righi, Cecilia; Maresca, Carmen; D’Avino, Nicoletta; Passamonti, Fabrizio; Giammarioli, Monica; Feliziani, Francesco; et al. (Frontiers in Microbiology, 2026)
Small ruminant lentiviruses (SRLVs) are retroviruses infecting small ruminants, characterized by a high genetic variability. SRLVs infection may result in a variety of clinical signs in goats and sheep and is not species-specific. SRLVs are worldwide distributed with four distinct genotypes and numerous sub-genotypes described so far. Full understanding of SRLVs epidemiology is still a matter of research and genetic characterization remains a key tool for unrevealing the complexity of such infections. A previous study, exploring the genetic landscape of SRLV in Italy, reported considerable genetic heterogeneity across geographic regions and suggested the presence of new sub-genotypes. In light of these previous results, our study provides an update on the genetic characterization of SRLVs based on phylogenetic analysis of SRLVs positive samples collected during passive surveillance in 16 out of 20 Italian regions between 2019 and 2024. Our findings revealed for the first time the broad genetic diversity of SRLVs circulating across Italy with apparently restricted circulation of some sub-genotypes to specific areas/regions. The observed genetic clusters are region-specific and do not align with the currently recognized sub-genotype nomenclature, suggesting that the existing classification system may necessitate an update to describe the current SRLVs diversity more accurately. Continuous monitoring through full gene and genome sequencing, coupled with an updated and expanded genetic classification framework, is essential for improving our understanding of this complex and evolving viral infection in small ruminants.